Challenges of implementing e-learning in art history faced by instructors and learners in Faculty of Art and Design, UiTM Perak / Nizar Nazrin, Farah Merican Isahak Merican and Syafiq Abdul Samat - Nizar, Nazrin; Farah Merican, Isahak Merican; Syafiq, Abdul Samat (Universiti Teknologi MARA, Perak, 2010)
There were arguments on the terminology of pedagogy and andragogy in education world where some says that pedagogy is the method of one teaching. In 1833, a German Teacher came with the term andragogy referring to adult teaching but were never look upon seriously till 1926 when Linderman made an extensive writing on it.